Characteristics of LiFePo4 and Li-Ion Batteries during the Process of Charging and Discharging for Recommendation Solar Power Energy Storage - Khairunnisa, Khairunnisa; Mafturoh, Siti Mita (DPTE FT UNY, 2023)
One of the advantages of using electric vehicle batteries to store electrical energy is an appropriate technology that supports zero emission. Hence, this research tries to compare based on each type of Lithium to be seen in terms of capacity and total energy obtained during charging and discharging conditions. The results of the comparison of the characteristics of the two batteries show that Lithium Iron Phosphate batteries have better quality. Based on the results of testing the conditions when charging from both of them, it was found that the capacity of the LiFePo4 battery was 22.93Ah while the Li-Ion was 2.65 Ah. for a total LiFePo4 energy of 79.84 Wh and Li-Ion of 10.28 Wh. Meanwhile, when testing the Discharging conditions, the LiFePo4 battery capacity based on the test results was 22.76 Ah and Li-Ion 2.60 Ah. Meanwhile, the measured total energy from LiFePo4 is 69.45 Wh, and Li-Ion is 9.44 Wh. Hence, if viewed from the advantages and disadvantages, Lithium Iron Phosphate batteries are suitable for accumulators or electric car batteries and energy storage for solar power plants